Pretreatment methods on Malaysian weedy grass (Pennisetum purpureum) for bioethanol production. - Liong, Yan Yee; Halis, Rasmina; Lai, Oi Ming; Mohamed, Rozi (2011)
Grasses are often regarded as weeds, yet they are abundant in lignocellulosic material. They can thrive throughout every climatic region, tolerate poor marginal soils and have no seasonal commitment. Here, we report the potential of a local Malaysian grass Pennisctum pirrpurmrn (Napier grass) as a biomass feedstock for bioethanol production. We compared two pretreatments on the raw plant material for the purpose of breaking-down lignin, a recalcitrant component in the fiber, which resist the release of cellulose in the plant cell wall. Lignin breakdown eventually enhances the efficiency of converting cellulose into glucose. Alkali pretreatment was carried out at four different NaOH concentrations: 1%, 5%, 7% and 10%. Alkali-pretreated materials were subjected to cellulase hydrolysis; several hydrolysis parameters were tested to optimize glucose yield including temperature and agitation, by applying the Response Surface Method (RSM). HPLC revealed that the glucose content in samples that were pretreated with 7% NaOH gave the highest yield (7.4 g/L). In addition, the glucose yield was not influenced by changes in hydrolysis parameters, therefore it was concluded as the most suitable pretreatment concentration. When using a white-rot fungus, Phanerochaebe chlysosporizrm as biological pretreatment followed by enzime hydrolysis, samples treated for the: weeks gave the highest glucose 1-ield (4.5 g/L). We demonstrated that Malaysian weedy grass is a potential lignocellulosic biomass that may serve as a cheap feedstock for bioethanol production.